2000
DOI: 10.1080/10473220050075635
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Ozone and Organic Volatiles from a Selection of Laser Printers and Photocopiers

Abstract: To estimate the impact of office equipment on the quality of indoor air, the emission of ozone and organic volatiles was measured from one photocopier and four laser printers, three of which operated according to traditional corona discharge technology. The laser printers equipped with traditional technology emitted significant amounts of ozone and formaldehyde. Lesser amounts of other volatile aldehydes were emitted during printing. The photocopier emitted mainly ozone. In a well-ventilated office environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…It should also be noted that the O 3 emission rates of these printers during monochrome printing were comparable to the results reported by Tuomi et al (2000) who tested 3 HP printers.…”
Section: Particle Emission Ratessupporting
confidence: 72%
“…It should also be noted that the O 3 emission rates of these printers during monochrome printing were comparable to the results reported by Tuomi et al (2000) who tested 3 HP printers.…”
Section: Particle Emission Ratessupporting
confidence: 72%
“…The operators are exposed to toner (while reloading and unloading the machines) and to toxic gases like ozone, nitrogen dioxide, volatile organic compounds and extremely low frequency electromagnetic fields during their operation [8][9][10][11][12] . Majority of these agents have been reported to be mutagenic or genotoxic in either bacterial or mammalian systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Some authors have reported that laser printers and photocopiers emit significant amounts of ozone, organic volatiles and formaldehyde during printing or operating process in a badly ventilated office environment, thus leading to oxidative stress and potential oxidative damage of the operators' bodies. [1,2] However, up to now, there are no reports on changes of free radical reactions in the bodies of photocopying operators (PO) who are working in the badly-ventilated office environments, nor reports about the relationship between oxidative stress and potential free radical damage associated with photocopying.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Some authors have reported that laser printers and photocopiers emit significant amounts of ozone, organic volatiles and formaldehyde during printing or operating process in a badly ventilated office environment, thus leading to oxidative stress and potential oxidative damage of the operators' bodies. [1,2] However, up to now, there are no reports on changes of free radical reactions in the bodies of photocopying operators (PO) who are working in the badly-ventilated office environments, nor reports about the relationship between oxidative stress and potential free radical damage associated with photocopying. To estimate the impact of photocopying on indoor air quality, to study oxidative stress and potential free radical damage to the PO bodies, and to explore a role for ozone emitted during photocopying process, 80 PO and 80 healthy volunteers (HV) were enrolled in a random control study design, in which the level of lipoperoxide (LPO, thiobarbituric acid reactive substances, TBARS) in erythrocytes and the levels of vitamin C (VC), vitamin E (VE) and b-carotene (b-CAR) in plasma as well as the activities of superoxide dismutase (SOD) and catalase (CAT) in erythrocytes were determined by spectrophotometric methods.…”
Section: Introductionmentioning
confidence: 99%